Mechanisms of Drug Release in Nanotherapeutic Delivery Systems - Wong, Pamela T; Choi, Seok Ki (Chemical reviews, 2015)
Wong and Choi examine mechanisms of drug release in nanotherapeutic delivery systems. They describe nanotherapeutics, nanocarriers, and biomarkers, along with their aims and scope. Their focus is then turned to the mechanisms of drug release via linker cleavage and the mechanisms of drug release via control of carriers. A summary of their conclusions is presented, along with potential challenges in nanotherapeutic linker design.